Selective Unilateral Spinal Anaesthesia for Outpatient Knee Arthroscopy Using Real-Time Monitoring of Lower Limb Sympathetic Tone. Issue 3 (May 2015) - Bergmann, I.; Hesjedal, B.; Crozier, T. A.; Pöschl, R.; Bauer, M.; Hinz, J. M.; Büttner, B.
Selective unilateral spinal anaesthesia is a useful approach for ambulatory lower limb surgery because it allows more rapid home discharge compared to bilateral block. Infrequent use is due to the fact that obtaining selective unilateral block can be difficult, requiring attention to technique. We present a method with a high success rate that uses real-time monitoring of the sympathetic activity of the legs. In this prospective study, 56 patients scheduled for ambulatory knee arthroscopy had spinal anaesthesia in the lateral recumbent position, with hyperbaric bupivacaine 0.5% injected at 0.33 ml/min up to a maximum dose of 5 mg. Sympathetic tone of the legs was monitored by plantar electrical dermal resistance. The clinical effect was assessed by loss of sensation and muscle strength. The haemodynamic course and adverse events were monitored. The motor block was strictly unilateral in 55 patients (98%) and the sensory block was strictly unilateral in 53 patients (94%). The median decrease in systolic blood pressure was 6 mmHg. The time from subarachnoid puncture to arrival in the recovery room was 73 ± 23 minutes; the duration of stay in the recovery room was 70 ± 30 minutes. Three patients with a well-established block of adequate extent required conversion to general anaesthesia because of tourniquet pain. Urinary retention only occurred in the sole patient with bilateral block. This method of performing selective unilateral spinal anaesthesia using real-time monitoring of sympathetic tone of the legs has a high success rate and is associated with rapid eligibility for home discharge.